Overview Of Elderly Knowledge Regarding Osteoporosis Prevention dan Treatment In Maradekaya Village,Gowa District - Fanny Dewi Sartika (Sean Institute, 2022)
Osteoporosis is a problem for the service system because the incidence of osteoporosis increases with age, and people adopt unhealthy lifestyles and reduce physical activity . This study aims to determine the knowledge of elderly people about preventing and treating osteoporosis in Maradekaya Village, Bajeng District, Gowa Regency. The type of research carried out was descriptive research. The sampling method used was accidental sampling. The research instrument used a questionnaire in the form of a check list. The results showed that 11.42% of respondents had good knowledge, and 22.85% of respondents had sufficient knowledge and the remaining 65.73% of respondents had poor knowledge. So it can be concluded that on average the elderly people in Maradekaya Village have insufficient knowledge about the prevention and treatment of osteoporosis